Notice of some Peruvian Antiquities obtained from a Burial-Mound at Arica. (With Photographs) (Proceedings of the Society of Antiquaries of Scotland, 1872)
The author describes a collection of artefacts unearthed from a burial mound by an earthquake in Peru and passed to him by a local antiquarian. He debates whether these burials can reveal anything about the culture of the people that created them and suggests that there may have been several periods of interment, based on the varied designs of some of the objects.